2000
DOI: 10.4049/jimmunol.164.5.2487
|View full text |Cite
|
Sign up to set email alerts
|

Maturation and Trafficking of Monocyte-Derived Dendritic Cells in Monkeys: Implications for Dendritic Cell-Based Vaccines

Abstract: Human dendritic cells (DC) have polarized responses to chemokines as a function of maturation state, but the effect of maturation on DC trafficking in vivo is not known. We have addressed this question in a highly relevant rhesus macaque model. We demonstrate that immature and CD40 ligand-matured monocyte-derived DC have characteristic phenotypic and functional differences in vitro. In particular, immature DC express CC chemokine receptor 5 (CCR5) and migrate in response to macrophage inflammatory protein-1α (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(105 citation statements)
references
References 35 publications
3
102
0
Order By: Relevance
“…Furthermore, adjuvants provide an Ag depot, allowing professional APCs to enter the vaccine site and collect the peptide. These Ag-loaded APCs then migrate to the lymph nodes and initiate T cell activation (22). This study presents evidence that the activating HPV16 E7 peptide persists in all organs longer than the tolerizing Ad5 E1A peptide as a result of a slow release of the HPV16 E7 peptide from the vaccine site (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, adjuvants provide an Ag depot, allowing professional APCs to enter the vaccine site and collect the peptide. These Ag-loaded APCs then migrate to the lymph nodes and initiate T cell activation (22). This study presents evidence that the activating HPV16 E7 peptide persists in all organs longer than the tolerizing Ad5 E1A peptide as a result of a slow release of the HPV16 E7 peptide from the vaccine site (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…It is demonstrated that CD40 stimulation induces the migration of DCs into secondary lymphoid tissues by up-regulating the expression of CCR7 (13,14). Indeed, CD40 stimulation for DCs is essential in the priming phase, since mice lacking CD40L showed defective priming ability accompanied by a disrupted migration of DCs for regional LNs (15).…”
Section: Endritic Cells (Dcs) 2 Are Believed To Be the Most Potentmentioning
confidence: 99%
“…To effectively deliver gold particles to the cytoplasm of epidermal LC it was necessary to use a He discharge pressure of 800 psi, which is four times higher than the pressure commonly used to transfect mouse or nonhuman primate skin. 8,21 Even with the application of a high pressure, gold particles were mostly found in the epidermis and only a few beads were detected in the epidermal/dermal junction. Accordingly, transgenic proteins were expressed mainly in the epidermis.…”
Section: (A) Most Of the Luciferase Expression Was Detected In Epidermentioning
confidence: 99%